Taâ€™thÄ«r á¹¬arÄ«qah al-TadrÄ«b (Drill Method) li al-Khaá¹ al-Ê¿Arabiy â€˜ala Jawdah al-KitÄbah laday al-TalÄmÄ«Å¼ bi MaÊ¿had HidayÄh al-Nas Bukit Batabuh - Refrensy, Desnely; Rizal, Eka (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The purpose of this thesis is to know the effect of using the training method (Drill) for Arabic calligraphy on the writing quality of students at Hidayat al-Nas Institute, Bukit Tabbouh, and the training method (Drill) is an attempt to improve Arabic calligraphy. The writing collects data for this research through field research using the experimental method with the quantitative research approach. Experimental research is research that attempts to conduct experiments to test hypotheses. The samples for this research are the Purposive sample. The writer used the experimental research, which is to reveal the promotion of the result of teaching Arabic calligraphy between the experimental class and the control class. As for the method of data collection, it is the test. The writer does the pre- and post-test for the experimental and control chapters, and the writer analyzes the information with aThe purpose of this research is to describe the effect of using the drill method for Arabic calligraphy on the writing quality of students at Hidayat al-Nas Institute, Bukit Batabuah, and the drill method is an attempt to improve Arabic calligraphy. The data collection for this research through field research uses experimental and quantitative research methods. Experimental research is research that attempts to conduct experiments to test hypotheses. The samples for this research are the Purposive sample. The writer used empirical research, which is to reveal the promotion of the result of teaching Arabic calligraphy between the experimental class and the control class. As for the method of data collection, it is the test. The writer does the pre-and post-test for the experimental and control chapters, and the writer analyzes the information with a T-test. The results of learning Arabic calligraphy for students before using this method were the increase in the average of the experimental class was 7.45, and the increase in the standard of the control class was 7.25. The average comparison range between the practical class and the control class is 0.20.Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ù‘Ø±Ø§Ø³Ø© Ù‡Ùˆ Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ (Drill Method) Ù„Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø¹Ù„Ù‰ Ø¬ÙˆØ¯Ø© ÙƒØªØ§Ø¨Ø© Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø¨Ù…Ø¹Ù‡Ø¯ Ù‡Ø¯Ø§ÙŠØ© Ø§Ù„Ù†Ø§Ø³ Ø¨ÙˆÙƒÙŠØª Ø¨ØªØ§Ø¨ÙˆÙ‡. Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ (Drill Method) Ù‡ÙŠ Ø£Ø³Ù„ÙˆØ¨ ØªÙ†Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ø¯Ø§Øª ÙˆØºØ±Ø³Ù‡Ø§ Ø¹Ù†Ø¯ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø¨Ø¹Ù…Ù„ÙŠØ© Ù…ØªÙƒØ±Ø±Ø© Ø¹Ù„Ù‰ Ø´ÙŠØ¦ Ù…Ø§ Ù„Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ø¨Ø±Ø§Ø¹Ø© ÙˆØ§Ù„Ø¯Ù‚Ø© ÙˆØ§Ù„ÙƒÙØ§Ø¡Ø©. ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù…Ù† Ø®Ù„Ø§Ù„ ØªØ¯Ø±ÙŠØ¨ ÙƒØªØ§Ø¨Ø© Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© Ø§Ù„ØªÙŠ ØªÙ‚Ø¹ ÙÙŠ Ø¨Ø¯Ø§ÙŠØ© Ø§Ù„ÙƒÙ„Ù…Ø© ÙˆÙˆØ³Ø·Ù‡Ø§ ÙˆÙ†Ù‡Ø§ÙŠØªÙ‡Ø§ØŒ ÙˆÙƒØ§Ù† Ø§Ù„ØªØ¯Ø±ÙŠØ¨ Ù…ØªÙƒØ±Ø±Ø§ ØØªÙ‰ ÙŠØ³ØªØ·ÙŠØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙƒØªØ§Ø¨Ø© Ø§Ù„ØØ±ÙˆÙ ØØ³Ø¨ Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ. ÙŠØ±ÙƒØ² Ø§Ù„Ø¨Ø§ØØ«Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¹Ù„Ù‰ Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù…Ø¹ÙŠÙ†Ø© Ø§Ù„ØªÙŠ ÙŠØ®Ø·Ø¦ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙƒØ«ÙŠØ±Ø§ Ø¹Ù†Ø¯ ÙƒØªØ§Ø¨ØªÙ‡Ø§. ÙˆØ§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ Ø¹Ø¨Ø§Ø±Ø© Ø¹Ù† Ù…ØØ§ÙˆÙ„Ø© ØªØØ³ÙŠÙ† Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ø¯Ù‰ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ°. Ø¬Ù…Ø¹Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¨ÙŠØ§Ù†Ø§Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…ÙŠØ¯Ø§Ù†ÙŠ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ø§Ù„Ø°ÙŠ ÙŠØØ§ÙˆÙ„ Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„ØªØ¬Ø§Ø±Ø¨ Ù„Ù…Ø¹Ø±ÙØ© ÙØ±Ù‚ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø¯Ø±Ø³ Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø¨ÙŠÙ† Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø·ØŒ ÙˆÙŠØªØ±ØªØ¨ Ø¨Ø¹Ø¯ Ø°Ù„Ùƒ Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ÙØ±Ø¶ÙŠØ©Ø› Ù…Ù‚Ø¨ÙˆÙ„Ø© ÙƒØ§Ù†Øª Ø£Ùˆ Ù…Ø±Ø¯ÙˆØ¯Ø©. Ø£Ù…Ø§ Ø£Ø³Ù„ÙˆØ¨ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙ‡Ùˆ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø±ØŒ ØªÙ‚ÙˆÙ… Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¨Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠ ÙˆØ§Ù„Ø¨Ø¹Ø¯ÙŠ Ù„Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø·ØŒ Ø«Ù… ØªØÙ„Ù„ Ø§Ù„Ø¨Ø§ØØ«Ø© Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ØªØ§Ø¦ÙŠ (t-test). Ø¨Ø¹Ø¯ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØªØªØØµÙ„ Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø¹Ù„Ù‰ Ø§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬ Ø£Ù† Ù‡Ù†Ø§Ùƒ ÙØ±Ù‚Ù‹Ø§ ÙƒØ¨ÙŠØ±Ù‹Ø§ ÙÙŠ ÙØ¹Ø§Ù„ÙŠØ© Ø¨ÙŠÙ† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ ÙˆØ§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠØ© Ù„ØªØØ³ÙŠÙ† ÙƒØªØ§Ø¨Ø© Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ø¯Ù‰ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø¨Ù…Ø¹Ù‡Ø¯ Ù‡Ø¯Ø§ÙŠØ© Ø§Ù„Ù†Ø§Ø³ Ø¨ÙˆÙƒÙŠØª Ø¨ØªØ§Ø¨ÙˆÙ‡. Ù…Ù† Ø®Ù„Ø§Ù„ Ù‡Ø°Ø§ Ø§Ù„ØªØÙ„ÙŠÙ„ØŒ ÙØªØ«Ø¨Øª Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø£Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ ÙØ¹Ø§Ù„ Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø®Ø· Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„Ù„ØªÙ„Ø§Ù…ÙŠØ°.